2019
DOI: 10.1186/s12906-019-2726-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, evaluation of nutritional parameters of Radix isatidis protein and its antioxidant activity in D-galactose induced ageing mice

Abstract: BackgroundRadix isatidis (Isatis indigotica Fort.) is an ancient medicinal herb, which has been applied to the prevention and treatment of influenza virus since ancient times. In recent years, the antioxidant activity of Radix isatidis has been widely concerned by researchers. Our previous studies have shown that Radix isatidis protein (RIP) has good antioxidant activity in vitro. In this study, the composition of the protein was characterized and its antioxidant activity in vivo was evaluated.MethodsThe model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…As the other ingredient in the mixture of Z. Tk , Radix isatidis is well-known for its broad antiviral activities and antioxidant properties. For example, it was reported that the proteins in R isatidis could eliminate the damage of free radicals, showing a strong antioxidant effect in vivo ( Xiao et al, 2019 ). Furthermore, ingredients, such as white peony polyphenols, isolated from R. paeoniae alba ( Zhou et al, 2019 ) and atractylenolides isolated from Atractylodes macrocephalae ( Bailly, 2020 ) are also effective antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…As the other ingredient in the mixture of Z. Tk , Radix isatidis is well-known for its broad antiviral activities and antioxidant properties. For example, it was reported that the proteins in R isatidis could eliminate the damage of free radicals, showing a strong antioxidant effect in vivo ( Xiao et al, 2019 ). Furthermore, ingredients, such as white peony polyphenols, isolated from R. paeoniae alba ( Zhou et al, 2019 ) and atractylenolides isolated from Atractylodes macrocephalae ( Bailly, 2020 ) are also effective antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…When the D-gal concentration exceeds normal level, it is converted to aldehydes and H 2 O 2 [ 32 , 33 ]. Animals injected with D-gal showed aging-related phenotypes, such as decreased immune responses, neurological defects, decreased antioxidant enzyme activity, increased ROS production and reproductive aging [ 14 , 34 36 ]. Ahangarpour et al used 500mg/kg D-galactose for six weeks and reported decreased sperm counts and increased serum LH levels in male mouse [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third important mechanism suggests galactose generates H2O2 by undergoing an oxidation reaction catalyzed by galactose oxidase (GO; EC 1.1.3.9) 17,18 and some researchers suggest that this is, in fact, the only metabolic route of galactose that produces reactive oxygen species (ROS) 21 . Interestingly, although a substantial number of researchers working with galactose-induced models of aging in rodents refer to GO-mediated generation of H2O2 as an important mechanism explaining the detrimental effects of galactose 17,18,[22][23][24][25][26][27][28][29][30][31][32][33][34] , this is a fungal enzyme that doesn't exist in rodents which makes these strong claims slightly suspicious as addressed in our recent comment 35 .…”
Section: Introductionmentioning
confidence: 93%